Cardiac and pulmonary thrombosis during multidrug treatment in an idiopathic thrombocytopenic purpura patient. (February 2014) - Andic, Neslihan; Gunduz, Eren; Akay, Olga Meltem; Şahin, Deniz; Teke, Hava Üsküdar
<x xml:space="preserve">Abstract</x> Glucocorticosteroids, intravenous immunoglobulins, vincristine, danazol, and eltrombopag are used in refractory chronic idiopathic thrombocytopenic purpura (ITP). All those treatment modalities are susceptible for thrombosis generation. There is an increased risk of thrombosis in the diseases' natural course. The case we present is a resistant chronic ITP patient who developed pulmonary and intracardiac thrombosis during multidrug treatment. Risk of concomitant usage of drugs and rapid increase in platelet count are discussed.